KORELASI NILAI ULANGAN HARIAN, NILAI ULANGAN TENGAH SEMESTER, DAN NILAI ULANGAN AKHIR SEMESTER, DENGAN NILAI RAPORT SEMESTER GASAL MATEMATIKA SISWA KELAS IV SD NEGERI 1 BAE KUDUS - Donny Anhar Fahmi, Maulana Alif Hidayat (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2014)
The background of this problem, namely the subjects of mathematics assessment that there is a discrepancy, such as the value of daily tests, mid-term test scores, final test scores, and the value of raport. Based on the SD 1 Bae which occurred in the fourth grade students daily tests, mid-term tests, final tests of the semester, and the value of the raport there was significant differences. It is proved to daily test values ?óÔé¼ÔÇ??óÔé¼ÔÇ?obtained good student, but the value of mid-term test, final test, and the value of raport do not correspond to the daily test value. Also occurs students?óÔé¼Ôäó daily test scores under KKM, but mid-term test values ?óÔé¼ÔÇ??óÔé¼ÔÇ?and high values ?óÔé¼ÔÇ??óÔé¼ÔÇ?above final test KKM, as well as the value of raport. The researchers tried to determine how much of a positive correlation between the value of daily tests, mid-term test, final test, and the raport. The problems revealed in this study is how much of the correlation between the daily tests, mid-term test scores, final test scores of Mathematics raport for the students of SD Negeri 1 Bae Kudus fourth grade.This type of the research used in this study is quantitative. Using the method of documentation of student. The population in this study that all students in the fourth grade students of SD Negeri 1 Bae Kudus. The samples in this study were 41 students. The study design used is by collecting student assessment data.Based on the results of the research, namely the value of daily tests, grades assignments, mid-term test scores, and test scores correlated with the value end of the semester raport. Correlations were used in this study is the product moment correlation. 1 rhitung obtained daily test of 0.685, 0.332 for daily tests 2, 3 daily test of 0.586, the value of 0,849 assignments, mid-term replicates of 0.973, 0.967 replicates at the end of the semester. rtabel consulted at the level of 5% with N = 41 is 0.308. It turns out that all rhitung> rtabel. So, the conclusion is there is a correlation between test scores for days 1, 2, 3, value assignments, mid-term test scores, test scores at the end of semester raport value. It is explained that the re is an increment or impairment of the daily tests value, grades assignments, mid-term test scores, and final test scores of the semester will be followed by increases and decreases in the value of raport. Then the researchers gave suggestions for how assessments are conducted properly.